Sociometry and spontaneous theater as methodologies for transformation and encounter: Young Costa Rican in contexts of violence - Páez-Brealey, Diego León (2016)
he purpose of this study is to show the theater of spontaneity (T.E.) and other innovative techniques for group and community action, as tools for research and social impact in different contexts. The text will deepen into the experiences of the T.E. company “UNA Compañía de Teatro Espontáneo”, working in a Becas Taller project from the Costa Rican Ministry of Culture and Youth called: “Ditsú: Jóvenes costarricenses como agentes de transformación social en contextos de violencia, una propuesta desde el teatro espontáneo” (Ditsú: Costa Rican Youth as agents of social transformation in contexts of violence, a proposal from the theater of spontaneity), a work developed in five high schools in communities with low human development index. The T.E. is a form of improvisational theater with theoretical and methodological foundations of sociometry and psychodrama, which uses aesthetic resources of the performing arts, dance and music. Unlike the classical theater proposal, the T.E. group does not perform with pre-written and practiced scripts, but the stories in scene will be told by the people who attend the presentation, who will have the chance to see them represented by a group of actors and actresses trained, along with a musician and a director or conductor. “UNA Compañía de Teatro Espontáneo” is an interdisciplinary group born at the National University of Costa Rica, with students of Psychology, Performing arts, International Relations, Philosophy and Sociology, and seeks to involve people as actors in their own processes of transformation.